SPAWNING BEHAVIOUR AND FECUNDITY OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER), AT MANGALORE - Rao, V Ramamohana (Indian Journal of Fisheries, 2011)
The earliest reference to the fecundity of the Indian mackerel was by Devanesan and John (1940) who estimated the number of ripe eggs in the mackerel ovary as 94,000. Subsequent work was directed mostly towards finding out the spawning behaviour of this fish, by the study of the intra-ovarian eggs. Pradhan (1956) indicated the possibility of the Indian mackerel spawning the eggs in successive batches over a prolonged period, like its Atlantic counter-part Scomber scombrus (L). Pradhan and Palekar (1956) described the maturity stages I to VII, based on the external appearance of the ovary, its size relative to the abdominal cavity, and the range of ova-diameter readings. However, they have not given any ova-diameter frequency polygons. Sekharan (1958) studied the ova-diameter frequency in a few ovaries of the mackerel, ranging in maturity stage from II-III to V-VI, VI-VII and a few spent ovaries. He stated that his investigation showed a possibility of the mackerel eggs ripening in batches and of their release in succession. Radhakrishnan (1962), adopting the method followed by Clark (1934), Prabhu (1956), and Qasim and Qayyam (1961), studied the ova-diameter frequency seasonally and indicated the possibility of the mackerel shedding its eggs in batches. Vijayaraghavan (1962) followed a different procedure. Employing very high magnification, he measured ova with diameter greater than 0.525 mm. Plotting this frequency with a small size interval (3.5^) he claims the modes were clearly distinguishable. These modes according to him were well-defined batches of eggs ripening in succession. Rao (1962) studied the ova-diameter frequency in maturity stages I-V and VII. However, spawn-ripe ovary corresponding to stage VI, as he stated, was not obtained in his study.